New records of millipedes and centipedes from Bulgaria, with an annotated checklist of the Bulgarian myriapods - Bachvarova, Darina; Vagalinski, Boyan; Doichinov, Aleksandar; Stoev, Pavel (Zootaxa, 2017)
The present paper records new and poorly known myriapods (Diplopoda, Chilopoda) collected in Bulgaria in the last 10 years. Four new species are reported as new to the Bulgarian fauna: Lithobius melanops Newport, 1845 (Chilopoda: Lithobiomorpha: Lithodiidae), Polydesmus collaris C.L. Koch, 1847, Polydesmus inconstans Latzel, 1884 and Polydesmus schaessburgensis Verhoeff, 1898 (Diplopoda: Polydesmida: Polydesmidae). Scanning electron micrographs of the gonopods and male leg-pairs 5 and 6 are provided for the first time for Bulgarosoma superficiei Strasser, 1975, a species hitherto known only from its original description. This article presents also an updated list of Myriapoda in Bulgaria. The list includes a total of 251 (sub-)species of the classes Diplopoda (127), Chilopoda (104), Pauropoda (18) and Symphyla (2).